Slow pyrolysis of maize stover for biochar Production - Seassey, Raymond (2014)
A thesis submitted to the Department of Chemical Engineering, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science (Chemical Eng.) .